Looking Through Someone Else's Eyes: Ethics, Terrorism and Identification in Jordi Évole's Documentaries: The Case of Don't Call Me Ternera (2023) - Iturregui-Motiloa, Víctor (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This article consists of an analysis of the documentary No me llame Ternera. Through a rewriting of the interview genre, the film proposes an ethical inquiry on the relationship between victims and perpetrators of ETA terrorism. The analysis goes along with a review of the political and media controversy before its release, as well as a brief comparison with other journalistic products made by Jordi Évole. Additionally, a theoretical framework has been accomplished regarding the representation in the media of individuals involved in crimes of blood, whether suffered or perpetrated.